Faktor-Faktor Yang Mempengaruhi Sikap Pemuda Terhadap Pekerjaan di Bidang Pertanian di Desa Selamat, Kecamatan Tenggulun, Kabupaten Aceh Tamiang - Safrida, Turti; Gustiana, Cut; Rozalina (Program Studi Agribisnis Fakultas Pertanian Universitas Samudra, 2025)
This study aims to find out what factors affect the attitude of youth towards work in agriculture in Selamat Village, Tenggulun District, Aceh Tamiang Regency. This type of research is a quantitative type. The population of this study is the youth of Selamat Village with the sampling technique used, namely the simple random sampling technique. The questionnaire measurement scale uses a likert scale that has been tested for validity and reliability. The data was processed using the help of 1BM Statistics 23 software using multiple linear regression analysis. The results of the study showed that the t-test carried out proved: 1) there was a negative and significant influence of age on youth attitudes towards jobs in agriculture (tcount -2,345 ttable > 1,688 and significance 0.025 < 0.050), 2) there was a positive and significant influence of formal education on youth attitudes towards work in agriculture (tcount 2,935 > ttable 1.688 and significant 0.006 < 0.050), 3) there was a positive and significant influence of land area on youth attitudes towards work in agriculture (tcount 7.768 > ttable 1.688 and significant 0.000 < 0.05), 4) there was a positive and significant influence of work socialization on youth attitudes towards work in agriculture (tcount 2.517 ttable 1.688 and significant 0.016 < 0.000), 5) there was an insignificant influence of information access on youth attitudes towards work in agriculture (tcount 0.435 < ttable 1.688 and significance 0.666 > 0.005). Meanwhile, the adjusted r square shows that the joint results between the variables tied to this study are 66.7% and the remaining 33.3% of the increase is influenced by other variables or factors that are not explained by this thesis research.